Missionary impositions: conversion, resistance, and other challenges to objectivity in religious ethnography - Crane, Hillary K.; Weibel, Deana L. (Lexington Books, 2012)
This book explores some of the less understood research considerations involved in studying religious populations with a missionary imperative. The essays encompass ethnographic fieldwork in Muslim, Christian, Buddhist, and other populations, addressing such topics as the fluidity of the anthropologist's own religious identity, objectivity versus subjectivity, the issue of reflexivity in ethnography, and the multi-positionality of the researcher